Factors Influencing Elementary School Teachers in Composing Final-Term Exam: A case study in the Bangka-Belitung Islands Province - M.Pd., Prayekti, Dra. (IJRDO- Journal of Educational Research, 2018)
This research was conducted in the Bangka-Belitung Islands Province with the purpose of identifying: (1) factors which cause teachers to experience difficulties in developing the final-term exam; (2) correlations between teachers’ education level, years of teaching, and their ability in composing the final-term test items; (3) efforts given by the local educational department and local government to help teachers write the final-term exam; and (4) impacts of the final-term exam which was made by the teachers on the students’ learning achievements. As many as 122 teachers were involved in this research as the respondents distributed in four different regional districts in the Bangka-Belitung Islands Province. The data were collected using a questionnaire as the primary data collection instrument. All of the responses from the 122 respondents were analyzed using a descriptive qualitative research method. From this research, it was concluded that: (1) factors which support the teachers’ readiness in developing the final-term exam include: (a) the teachers’ experience in joining trainings in designing tests, (b) motivation given by the headmaster, (c) contribution from the handout as the main source of reference in writing the test, (d) support from the school inspector, and (e) availability of the blueprint of the final-term test design; and (2) obstacles which were experienced by the teachers in developing the final-term test consisted of (a) the lack of motivation to write the final-term exam due to the fact that there was only 50% of the subject materials were selected and used in the final-term exam, and (b) lack of training opportunities in designing a good quality test; also, (3) efforts given by the teachers in order to prepare themselves in designing the final-term exam comprised: (a) reading the handout and resource book of the test materials, (b) asking for some guidance from the supervisors who are considered to be the experts in their field, (c) initiating cooperation with teachers from other elementary schools, and (d) improving the strong level of confidence on the good quality of the final-term exam questions which were already composed. The suggestions proposed were: (1) the teachers had to be provided with adequate training opportunities to write a good quality of a final-term exam, and (2) as this research reached out the 122 teachers as the respondents, therefore, there was an urgent need to conduct a more comprehensive research study with more respondents to be involved.